Data Resource Profile: The Disability Statistics - Estimates Database (DS-E Database). An innovative database of internationally comparable statistics on disability inequalities - Carpenter, Bradley; Kamalakannan, Sureshkumar; Patchaiappan, Kaviyarasan; Theiss, Katherine; Yap, Jaclyn; Hanass-Hancock, Jill; Murthy, GVS; Pinilla-Roncancio, Monica; Rivas Velarde, Minerva; Mitra, Sophie (International Journal of Population Data Science, 2024)
Introduction The Disability Statistics (DS) Database provides internationally comparable statistics to monitor the rights of persons with disabilities. The Disability Statistics – Estimates (DS-E) Database includes national and subnational descriptive statistics based on the analysis and disaggregation of national population and housing censuses and household surveys. The database can inform policies and programs to advance the rights of persons with disabilities. Methods As of 2024, the DS-E Database includes estimates for 29 indicators providing information on the prevalence of disability and associations with education, personal activities, health, standards of living, insecurity, and multidimensional poverty. Estimates are based on 53 national datasets, including 23 population and housing censuses and 30 household surveys for 40 countries. The results were disaggregated by type and severity for adults and population subgroups (women, men, rural and urban residents, age groups 15 to 29, 30 to 44, 45 to 64, 65 and older). Estimates are also available at the first subnational level for all countries and at the second subnational level for 17 countries. Results At the time of publication, the DS-E Database includes 40 countries and 6,584 subnational locations, with more than 4.3 million estimates of indicators by disability status for adults and population subgroups. Results are in an interactive platform and in downloadable tables where both means and standard errors are available. The DS-E Database results indicate consistent inequalities within and across countries that show that persons with disabilities are more likely to experience deprivations and multidimensional poverty. Conclusion The DS-E Database provides statistics on the disparities people with disabilities experience, which can be used to support advocacy for disability-inclusive policy and practice. It provides statistics on outcomes such as education, health, employment. Outcomes can be matched with environmental, service delivery and other datasets to provide insights into, for example, where people with disabilities are left behind and where services are needed.